METABOLIC REMODELING AFTER BARIATRIC SURGERY IN IRAQ: BIOMARKER-LINKED OUTCOMES STRATIFIED BY NAFLD SEVERITY AND METABOLIC SYNDROME AT 3 YEARS - Melek, Hassan Khalil (PT. Antis International Publisher, 2025)
Objective: To complete 3 year prospective assessment of clinical and molecular outcomes after Roux-en-Y gastric bypass (RYGB) and sleeve gastrectomy (SG) in Iraqi patients, respectively, with the express links between the weight loss curves, comorbidity improvement, and the serial profiling of the major metabolic biomarkers. Method: The present study was a multicenter prospective cohort study carried out between January 2020 and December 2023 in the Al-Zahraa and Al-Karama Teaching Hospitals in Wasit, Iraq. The number of patients (RYGB: n=120; SG: n=120) followed in the 36 months was 240. Primary outcomes: percent excess weight loss (%EWL), type 2 diabetes mellitus (T2DM; HbA1c <6.5% off medication) remission and improvement of non-alcoholic fatty liver disease (NAFLD) (improvement in CAP score at least 30% by FibroScan). Secondary outcomes: postoperative complications (Clavien-Dindo classification) and preoperative and 12 and 36 months serial quantification of biomarkers: leptin, total ghrelin, adiponectin, active GLP-1, HOMA-IR, and QUICKI. Statistical methods were done in SPSS v28 and R v4.3 with multivariate logistic regression and Pearson correlation. Results: RYGB showed much better percent EWL (77.1% +12.8 vs. 68.3% +14.5; p=0.004), T2DM remission (81.2 vs. 67.5; p=0.025), and NAFLD improvement (85.0 vs. 71.7; p=0.015) at 36 months. Biomarker examination showed that RYGB led to much more pronounced leptin (': -34.5 vs. -27.6 ng/mL; p=0.005) and adiponectin (': +5.5 vs. +3.4 0g/mL; p=0.003) and active GLP-1 (': +17.8 vs. +9.1 pmol/L; p<0.001) decreases. The remission of T2DM was independently predicted by preoperative adiponectin >5 μg/mL (OR 2.9, 95% CI 1.366.1; p=0.007). RYGB offered more absolute metabolic benefit to patients with baseline MetS + (n=165). Patients who have severe NAFLD (CAP ≥310 dB/m) had a much greater improvement using RYGB compared to SG (62.9% vs. 40.5%; p=0.04). An index of composite adiponectin/HOMA-IR above 0.75 was a predictor of 90% remission following RYGB (AUC 0.86). Significant complications (Clavien-Dindo ≥III) were equal (RYGB 8.3% vs. SG 5.8%; p=0.45). Novelty: This is the inaugural Iraqi investigation to correlate length of surgical results with sequence serially of biomarkers to propose, albeit the constraints of its observational design, a platform of biomarker-managed, customized metabolic surgery in the area.